Analyzing technological component of manufacturing international special purpose products (by example of space industry) - Омельяненко, Віталій Анатолійович (Technology audit and production reserves, 2014)
The peculiarities of producing international special purpose products by the example of space industry are considered in the paper, and some of the research results in this field are given. The main objective of the research lies in developing theoretical bases of prioritizing the industry in terms of its international specificity. Using modern methods of decision-making when choosing technology priorities based on a foresight and a socio-economic forecasting allows providing both competitive advantages in global industries and development of the national economy thanks to a cross-sectoral technology transfer. The peculiarities of choosing technology priorities based on a life cycle theory and technology parameters are considered in the paper. The given technique allows obtaining evaluation data using tools for analyzing development alternatives. The algorithm for selecting research papers from a list of projects has been developed. These research papers are offered for executing a scientific and technological program within the scope of a respective section, related to the space industry. The research results can be used by experts for substantiating the innovative development priorities of the industry.